Enhancing EFL Students’ Speaking Skills Through the Debate Technique: A Classroom Action Research Study - Oktaviani, Anggit Laesa; Rapiudin, Tubagus Udong; Mahyati, Mahyati; Supriyanto, Edy; Suryadi, Asep (English Education Department at FKIP Nommensen University, 2025)
This study aims to analyze the implementation of the debate technique in improving students’ speaking skills and to assess the outcomes after its application. Conducted in class XI A3 of SMAN 19 Tangerang Regency, the research involved 36 students and employed Classroom Action Research (CAR) through two cycles. Data was collected via observation, documentation, and speaking tests, and analyzed using both quantitative and qualitative methods. The population of this research is 180 students in the XI science classes, while for the samples, the researcher selected 36 students from XI A3 because this class is considered to be the most passive one compared to others . xxxxx The findings revealed that the debate technique was effective in enhancing students’ speaking performance, self-confidence, and classroom interaction. The pre-test score was 62 . These improved to 68.67 in the in cycle one. In the cycle 2, students exceeded the minimum passing score, achieving 76.89. The results indicate that debate is a beneficial and engaging technique for fostering speaking skills in an EFL context. It is recommended that teachers integrate debate activities into their instruction to encourage student participation, critical thinking, and oral communication. Yet, the improvement on the pronunciation needs more exploration for the next research.